Development of a smartphone-based quantum dot lateral flow immunoassay strip for ultrasensitive detection of anti-SARS-CoV-2 IgG and neutralizing antibodies. (August 2022) - Li, Jinfeng; Liu, Bochao; Tang, Xi; Wu, Ze; Lu, Jinhui; Liang, Chaolan; Hou, Shuiping; Zhang, Ling; Li, Tingting; Zhao, Wei; Fu, Yongshui; Ke, Yuebin; et al.
Highlights: Quantum dot lateral flow immunoassay QD-LFIA was established for the detection of specific IgG and NAb to SARS-CoV-2. The QD-LFIA was based on smartphones. The QD-LFIA is ultrasensitive, cost-effective, rapid, and simple. The QD-LFIA can be used for on-site detection in clinical practice. ABSTRACT: Background: As several vaccines for SARS-CoV-2 have been developed, a large proportion of individuals have been vaccinated worldwide so far. The rapid and accurate immunoassays are urgently needed for detecting the specific virus-neutralizing antibody (NAb), which reflect the protective effect of the vaccines among different populations. Methods: In this study, we designed a quantum dot lateral flow immunoassay strip (QD-LFIA) for smartphones for the detection of specific IgG or neutralizing antibodies in SARS-CoV-2 in human serum or whole blood samples. The recombinant receptor binding domain of the SARS-CoV-2 spike protein was used as the antigen to combine with NAb or angiotensin-converting enzyme 2. Results: Among 81 patients who recovered from COVID-19 who were diagnosed using the nucleic acid test initially, 98.8% (80/81) were positive for IgG and 88.9% (72/81) were positive for NAb by QD-LFIA. Among 64 individuals inoculated with inactivated vaccines and six subunit vaccines, 90% (63/70) were positive for IgG and 82.9% (58/70) were positive for NAb by QD-LFIA, whereas no cross-reaction was found in 150 healthy blood donors, two patients with influenza B, and three patients with common cold. Conclusion: The established platform could achieve a rapid and accurate detection of NAb specific to SARS-CoV-2, which could be used for detecting the protective effect of the vaccines in areas of world that currently affected by the pandemic.